Cytotoxic CD8+ T Cells Expressing CXCR5 Are Detectable in HIV-1 Elite Controllers After Prolonged In Vitro Peptide Stimulation - Adams, Philipp; Iserentant, Gilles; Servais, Jean-Yves; Vandekerckhove, Linos; Vanham, Guido; Seguin-Devaux, Carole; , the PhenoCure Study Group (Frontiers in Immunology, 2021)
Antiretroviral therapy (ART) is not curative as HIV-1 persists in long-lived viral reservoirs. Consequently, patients are dependent on life-long drug adherence with possible side effects. To overcome these limitations strategies of a functional cure aim at ART free viral remission. In this study, we sought to identify detailed subsets of anti-viral CD8+ T cell immunity linked to natural long-term control of HIV-1 infection. Here we analyzed HIV controllers and ART suppressed progressors for in vitro viral suppressive capacity (VSC) at baseline and after prolonged peptide stimulation. Functional properties and phenotypes of CD8+ T cells were assessed by IFN-γ ELISPOT and 18 color flow cytometry. HIV controllers showed significantly increased suppression at baseline as well as after prolonged peptide stimulation. IFN-γ secretion and the proliferation marker Ki67 positively correlated with VSC. Moreover, the detailed phenotype of three distinct multifunctional memory CD8+ T cell subsets were specific traits of HIV controllers of which two correlated convincingly with VSC. Our results underline the importance of multifunctional CD8+ T cell responses during natural control. Especially the role of CXCR5 expressing cytotoxic subsets emphasizes potential surveillance in sites of reservoir persistence and demand further study.